Does Pandanus thwaitesii Mart. occur in India? - Bhat, K. G (Rheedea, 1997)
Pandanus thwaitesii Mart. does not appear to occur in India and specimens identified and reported as P. thwaitesii from South India belong to P. foetidus Roxb.